Handbook of Behavior, Food and Nutrition 2011
DOI: 10.1007/978-0-387-92271-3_201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Body Image During Adolescence

Abstract: Abbreviations BMI Body mass index SEM Structural equation modeling SES Socioeconomic status IntroductionOver the years, research has implicated a number of developmental (e.g., pubertal timing), psychological (e.g., self-esteem), and sociocultural (e.g., culturally-defined and transmitted messages regarding attractiveness) factors in the development and maintenance of body image disturbance and related issues in adolescents. In this chapter, we will focus exclusively on sociocultural factors that affect adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
0
9
0
2
Order By: Relevance
“…Adolescence is a period of life characterized by many important physical and psychological changes that may influence the identity development (Harter 2003 ; Alsaker and Flammer 2006 ; Smolak and Stein 2010 ; Fenton et al 2010 ; Confalonieri and Gatti 2011 ). Since many studies have shown that the most important individual factors influencing the sense of identity in adolescence are age and sex (Holmqvist and Frisen 2012 ; Weichold and Fasche 2010 ; Ata et al 2011 ; Gatti et al 2014 ), and these factors are related also to avatar appearance in adult samples (Martey et al 2013 ; Reed and Fitzpatrick 2008 ; Beasley and Standley 2002 ), we first investigated whether these factors influence the adolescent virtual self-representation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescence is a period of life characterized by many important physical and psychological changes that may influence the identity development (Harter 2003 ; Alsaker and Flammer 2006 ; Smolak and Stein 2010 ; Fenton et al 2010 ; Confalonieri and Gatti 2011 ). Since many studies have shown that the most important individual factors influencing the sense of identity in adolescence are age and sex (Holmqvist and Frisen 2012 ; Weichold and Fasche 2010 ; Ata et al 2011 ; Gatti et al 2014 ), and these factors are related also to avatar appearance in adult samples (Martey et al 2013 ; Reed and Fitzpatrick 2008 ; Beasley and Standley 2002 ), we first investigated whether these factors influence the adolescent virtual self-representation.…”
Section: Discussionmentioning
confidence: 99%
“…The construct of virtual self-discrepancy has been associated with users’ dissatisfaction with real life (Alsaker and Kroger 2006 ) and users’ intention to gain better mastery of the virtual world (Anderson et al 2004 ). On the other hand, some researchers maintain that an avatar customized by an individual is substantially an extension of his or her self (Ata et al 2011 ; Beasley and Standley 2002 ; Bell and Dittmar 2011 ), in that the avatar can be considered an expression of the individual’s actual identity (Bernasconi 2009 ; Bessiere et al 2007 ). This coherence between individuals and their avatars have been found both related to personality, mental states, self-esteem and interests (Fong and Mar 2015 ; Kafai et al 2010 ; Park and Henley 2007 ; Dunn and Guadagno 2012 ) and to behaviors exhibited within the virtual environment (Bessiere et al 2007 ; McCreery et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of the family environment, parents are strong communicators of appearance ideals and exert appearance-related pressures through direct appearance-related comments and modeling of appearance concerns (Ata, Rojas, Ludden, & Thompson, 2011). Indeed, research suggests that such parental pressures exhibit considerable influence on sons' and daughters' body image and eating behaviors (Bearman, Presnell, Martinez, & Stice, 2006;Rodgers & Chabrol, 2009).…”
Section: Development and Validation Of The Sataq-4 5 Development And mentioning
confidence: 99%
“…Salah satu faktor sosial yang paling berpengaruh terhadap berkembangnya body dissatisfaction adalah media massa. Media berkontribusi pada body image dengan cara menyebarkan pesan terkait bagaimana sosio-budaya memandang daya tarik yang ideal yang seharusnya dimiliki individu (Ata, Rojas, Ludden, & Thompson, 2011). Paparan tentang bentuk tubuh yang dianggap ideal pada media menimbulkan adanya body dissatisfaction.…”
Section: Pendahuluanunclassified